Effect of oral nitrate on time-trial performance in severe hypoxia: A randomized placebo controlled trial - Bourdillon, N.; Fan, J. L.; Muller, H.; Meyer, P.; Kayser, B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Dietary nitrate as salt or in nitrate-rich food like beet root juice is a precursor for nitric oxide (NO). Nitrate may improve aerobic performance, through improved oxidative metabolism and contractile efficiency (Larsen et al. 2011). NO also contributes to adjust pulmonary arterial tone. Aerobic exercise in severe hypoxia (>4500m) may be limited by hypoxic pulmonary vasoconstriction (HPV). We tested the hypothesis that oral intake of nitrate in hypoxia limits HPV, improves right heart function, and thus allows better maximum time-trial cycling performance. Methods: We examined the effect of 3-day oral nitrate supplementation (0.1 mmol/kg/day) vs. placebo (randomized, double blind) in 11 well-trained cyclists (VO2max: 63.3±6.6 mL/kg/min) on a) middle cerebral artery velocity (MCAv), cerebral and muscle oxygenation (O2Hb & HHb), VO2 and performance of 15 km time trial cycling (TT) in normoxia and hypoxia (FIO2: 0.11, 5000m) and b) right ventricular systolic pressure (RV-RA gradient) and function (TAPSE, S-wave) estimated by echocardiography at rest and during submaximal normoxic/hypoxic exercise (50, 100, 150 Watts). We further measured resting expired NO at rest. Results: Nitrate had no effect on expired NO (P>0.05). Hypoxia reduced TT performance by 23 ± 9%, lowered VO2, cerebral and muscle O2Hb and elevated MCAv (P<0.05). Nitrate had no effect (P>0.05). During steady-state exercise in hypoxia the changes in TAPSE, RV-RA gradient and S-wave were suggestive of increased pulmonary arterial pressure; Nitrate elevated systemic diastolic blood pressure by 7.5 +/- 2.1 mmHg across all intensities (P<0.05) but had no effect on other parameters. Discussion: Contrary to our hypothesis oral nitrate intake in well-trained cyclists did not improve time-trial cycling performance, nor reduce the oxygen cost of exercise, either in normoxia or hypoxia. Since most other studies in the literature reporting improved oxidative metabolism with nitrate where not done with well-trained athletes, we speculate that training status of the subjects may interfere with nitrate effects. Conclusion: Our findings contrast with the literature and question the routine use of oral nitrate as a means to improve aerobic exercise performance, in normoxia or hypoxia, in well-trained endurance athletes.